(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Continuing professional development of teacher educators today is crucial to preparing the teachers of tomorrow. It is a known fact that the quality and extent to which a learner achieves are majorly determined by factors like teacher competence, teacher motivation and sensitivity, therefore teacher educators are an important factor in the education system. The purpose of the study is to develop an understanding of relationship between professional development and job satisfaction of teacher educators. A sample of 120 teacher educators from colleges of education with 50 teacher educators working in government and government aided colleges and 70 teacher educators working in private college was drawn from 12 randomly selected colleges of education of Punjab state. A significant positive relationship was found between professional development and job satisfaction of teacher educators working in both government and private sectors.